ABOUT COMMUNICATION BETWEEN TRANSCENDENTAL NUMBERS e AND п - Anatoly M. Makarov (Современная наука и инновации, 2022)
In the message the approach to defining the relationship between the fundamental con-stants: algebraic constant e and geometric constant p .